\(\sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6++...+\sqrt[3]{6}}}}< 2\)
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

NV
13 tháng 1 2019

\(D=\sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{6+\sqrt[3]{6}}}}}\)

\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{6+\sqrt[3]{8}}}}}\)

\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{6+2}}}}\)

\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{8}}}}\)

\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{8}}=\sqrt[3]{6+2}=\sqrt[3]{8}\)

\(\Rightarrow D< 2\) (đpcm)

17 tháng 5 2017

đừng chửi mik nha, mik ms hk lp 7 àk

20 tháng 8 2017

\(\sqrt{7}-\sqrt{3}=\frac{4}{\sqrt{7}+\sqrt{3}}< \frac{4}{\sqrt{6}+\sqrt{2}}=\sqrt{6}-\sqrt{2}.\)

\(\frac{3}{2}\sqrt{6}+2\sqrt{\frac{2}{3}}-4\sqrt{\frac{3}{2}}=\frac{3}{2}\sqrt{6}+\frac{2.1}{3}\sqrt{2.3}-\frac{4.1}{2}\sqrt{3.2}\)

\(=\frac{3}{2}\sqrt{6}+\frac{2}{3}\sqrt{6}-2\sqrt{6}=\sqrt{6}\left(\frac{3}{2}+\frac{2}{3}-2\right)\)

\(=\sqrt{6}\left(\frac{9}{6}+\frac{4}{6}-\frac{12}{6}\right)=\sqrt{6}.\frac{1}{6}=\frac{\sqrt{6}}{6}\)

Vậy \(\frac{3}{2}\sqrt{6}+2\sqrt{\frac{2}{3}}-4\sqrt{\frac{3}{2}}=\frac{\sqrt{6}}{6}\)